Pengaruh Suhu Annealing dan Konsentrasi MgCl2 terhadap Spesifisitas Amplikon dengan Primer CSSM018 - Indriawati, Indriawati; Margawati, Endang T. (Universitas Atma Jaya Yogyakarta, 2009)
Polymerase chain reaction (PCR) is a technique of DNA amplification which its success depends on the wider range of several factors, e.g., the annealing temperatures and MgCl2 concentrations. The aim of this study was to determine the effect of annealing temperatures and MgCl2 concentrations on the amplicon specificity of CSSM018 primer. Annealing temperatures of 50oC to 60oC were used in this study while MgCl2 concentrations were in the range of 1.0mM to 2.5 mM. DNA genome of Garut sheep was used as DNA template. PCR products were visualized by a method of 8% ND PAGE. The findings showed that the annealing temperature of 60oC presented the most specific band of the CSSM018 primer at the right size of 116-134bp. Annealing temperatures that were less than 60oC showed the weaker and non-specific bands. A concentration of 1.25 mM MgCl2 showed the best band of the CSSM018 primer with size of 116-134bp. While concentrations of 1.5; 1.75; 2.0 and 2.5 mM MgCl2 showed sharper with some bands seemed noisy, those indicated non-specific products. This study suggests that annealing temperature of 60oC and MgCl2 concentration of 1.25 mM resulted specific amplicon for CSSM018 primer.